Bimbingan Teknis Senam Lantai pada Kegiatan Ekstrakurikuler Murid SD Negeri 3 Jeumpa Kabupaten Bireuen - Aceh - Tawakal, Tawakal; Hidayat, Syukran; Cahyadi, Agung (LPPM Umuslim, 2024)
Floor gymnastics itself is included in the group of artistic gymnastics, which is a combination of tumbling and acrobatic aspects to obtain artistic effects with perfection of movement in controlling the body when carrying out various positions and movements carried out on certain equipment. Therefore, basic guidance on exercise is needed, rules and how to do it so that it is not risky. So, technical guidance on floor exercise was carried out for students in grades V and IV of elementary school with the aim of improving gymnastics skills with technical guidance strategies to fill extracurricular activities using the directing method with video presentations, demonstrations and group exercise, where the servants played a direct role as instructors. The results show an increase in training, rules in floor exercise and ways to avoid risks due to exercise containing dangerous movements.